The Political Possibilities of an Administrative Boundary: How the Transforming M-Ward Project 'Constructed' the Ward. (November 2020) - Bhide, Amita
This article reflects on the significance of an administrative boundary in producing distinctive forms of political assertion. It shows how acts of highlighting the ward boundaries of a marginal suburban ward in Mumbai illuminated an important scale of discriminatory spatial governance and also helped its residents organise and articulate a new politics of infrastructural need at a significant planning scale.